2018
DOI: 10.1016/j.cortex.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory performance in aphantasia

Abstract: Aphantasia, i.e., the congenital inability to experience voluntary mental imagery, offers a new model for studying the functional role of mental imagery in (visual) cognition. However, until now, there have been no studies investigating whether aphantasia can be linked to specific impairments in cognitive functioning. Here, we assess visual working memory performance in an aphantasic individual. We find that she performs significantly worse than controls on the most difficult (i.e., requiring the highest degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
105
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 28 publications
(34 reference statements)
10
105
1
Order By: Relevance
“…This evidence is consistent with classical neuropsychological evidence of severe visual agnosia in the absence of imagery deficit (Behrmann et al, ) as well as of representational neglect in the absence of extrapersonal perceptual neglect (Guariglia, Palermo, Piccardi, Iaria, & Incoccia, ). They also open new fascinating possibilities toward the understanding of new discovered disorders of mental imagery such as congenital aphantasia (Fulford et al, ; Jacobs et al, ; Keogh & Pearson, ; Watkins, ; Zeman et al, , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence is consistent with classical neuropsychological evidence of severe visual agnosia in the absence of imagery deficit (Behrmann et al, ) as well as of representational neglect in the absence of extrapersonal perceptual neglect (Guariglia, Palermo, Piccardi, Iaria, & Incoccia, ). They also open new fascinating possibilities toward the understanding of new discovered disorders of mental imagery such as congenital aphantasia (Fulford et al, ; Jacobs et al, ; Keogh & Pearson, ; Watkins, ; Zeman et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…However, neuropsychological evidence of severe visual agnosia in absence of imagery deficit (Aglioti, Bricolo, Cantagallo, & Berlucchi, ; Behrmann, Winocur, & Moscovitch, ; Riddoch & Humphreys, ), as well as evidence for a selective acquired (Guariglia, Padovani, Pantano, & Pizzamiglio, ; Trojano & Grossi, ) or congenital deficit in generating mental images (Fulford et al, ; Jacobs, Schwarzkopf, & Silvanto, ; Keogh & Pearson, ; Watkins, ; Zeman, Dewar, & Della Sala, , ), inevitably points toward a dissociation between imagery and perception. Neuroimaging studies show that information about the object category can be decoded based on the activity patterns within the HVC during both imagery and perception, but only during perception based on the activity patterns of the low‐level visual cortex (LVC; i.e., the retinotopic cortex/lower visual areas; Reddy, Tsuchiya, & Serre, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, beyond this, little research has examined the nature of aphantasia and the impact on imagery function and cognition more broadly. A single-participant aphantasia case study found no significant difference from controls in a visual imagery task (judging the location of a target in relation to an imagined shape) nor its matched version of a working memory task, except at the hardest level of difficulty [5]. However, aphantasics show significantly less imagery-based priming in a binocular rivalry task [2, 15], and show diminished physiological responses to fearful text as compared with controls [7].…”
Section: Introductionmentioning
confidence: 99%
“…The subjective vividness of visual mental images varies substantially across individuals [2][3][4][5] . Some individuals experience mental images as "quasivisual" in nature, while others have less vivid images, down to the total absence of VMI experience in otherwise normal individuals, a condition dubbed as "aphantasia" [6][7][8][9] . The neural bases of this remarkable set of cognitive functions are the object of intense research efforts 3,10-15 .…”
Section: Introductionmentioning
confidence: 99%